Life-time HIV testing among people who inject drugs in Iran: results from the National Rapid Assessment and Response survey - Roshanfekr, Payam; Karimi, Salah Eddin; Narouee, Sakineh; Moftakhar, Leila; Vameghi, Meroe; Ali, Delaram; Higgs, Peter; Soleimanvandiazar, Neda (Frontiers in Public Health, 2023)
Background: HIV testing is recommended for people who inject drugs (PWID). The aim of this study was to determine the prevalence of lifetime HIV testing among PWID and to better understand the predictors for HIV testing in a convenience sample across Iran. Material and Methods: This study is a secondary analysis of Iran's national Rapid Assessment and Response survey conducted between October 2016 and March 2017. Analysis includes the 999 people who reported injecting drugs across the capital cities of 21 provinces. Data were collected by using the venue-based application of the Time Location Sampling (TLS) frame. Chi-square tests were used to examine the difference between HIV testing across different quantitative variables. Logistic regression was used to determine the predictors of life-time HIV testing. Analysis was performed using STATA V.12 software with a significance level of 95%. Results: Most participants were male (n=902, 93.50%), and over half (n= 555, 59.17%) were older than 35 years old. About one-third, (n=326, 38%) of people interviewed were single and another one-third (n=251, 29%) reported being divorced. Over two-thirds of participants (n=678, 69.78%) in this study reported lifetime HIV testing. The results from a multiple variable logistic regression showed people with a university education were more likely to have been previously tested for HIV than illiterate people (OR= 18.87, 95%CI 2.85-124.6, p-value=0.002). Those individuals who reported ever receiving methadone treatment were 2.8 times more likely to have been tested for HIV than individuals without methadone treatment experience (OR= 2.89, 95%CI 1.53-5.42, p-value<0.001). Needle syringe sharing in last month, was negatively associated with life-time HIV testing (OR= 0.29, 95%CI 0.17-0.48, p-value<0.001). Conclusion: Despite Iran’s wide availability and access to counseling services for HIV testing in key populations, the proportion of PWID being tested for HIV could be improved. Developing effective strategies to increase people's understanding and awareness of the importance of and need for HIV prevention and familiarity with HIV testing sites is an essential step in increasing HIV testing for this population. Studies on more recent HIV testing are required to better assess and understand the frequency of HIV testing among PWID in Iran.